2022
DOI: 10.1155/2022/8512374
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effect of Laminectomy with Lateral Mass Screw Fixation in Treating Cervical Schwannoma: A Retrospective Study

Abstract: Background. The objective of this study was to evaluate the clinical effectiveness and safety of laminectomy combined with lateral mass screw fixation in treating cervical intradural extramedullary schwannoma. Methods. We retrospectively collected and analyzed medical records of 38 patients who underwent resection of cervical intraspinal schwannoma between January 2012 and April 2019. Based on different surgical procedures, two groups were divided among all participants: laminectomy-only ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In fact, Jinnai, et al, had 100% GTR for all C1-C2 lesions [27]. Nonetheless, surgical resection is associated with significant improvements in patient-reported outcomes and satisfaction [33,34].…”
Section: Surgical Resection and Complicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, Jinnai, et al, had 100% GTR for all C1-C2 lesions [27]. Nonetheless, surgical resection is associated with significant improvements in patient-reported outcomes and satisfaction [33,34].…”
Section: Surgical Resection and Complicationsmentioning
confidence: 99%
“…There are several studies that investigate the role of arthrodesis in cervical schwannomas. Laminectomy combined with lateral mass screw fixation is associated with less subsequent spinal instability and deformity compared to laminectomy alone [34]. Furthermore, Sebai, et al, found that total facetectomy was associated with a greater odds of the addition of arthrodesis compared to subtotal facetectomy, likely due to concern about spinal instability [47].…”
Section: Surgical Resection and Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 The thin lamina and anatomical variability in the C3-C6 segments limit the application of translaminar screw fixation techniques. 9 Conversion to a pedicle screw and revision attempt of the fixation trajectory increased neurovascular injury risk because the small and narrow pedicles are surrounded by vital anatomical structures, such as the central spinal cord, nerve roots, and anterolateral vertebral artery. 10 Several research recommends using polymethylmethacrylate (PMMA) to strengthen the bone-implant interface in the osteoporotic spine and as salvage options for thoracolumbar pedicle screw loosening.…”
Section: Introductionmentioning
confidence: 99%
“…A different approach and change in surgical position are required for anterior fixation, and potential morbidities such as nerve root injuries may occur 8 . The thin lamina and anatomical variability in the C3–C6 segments limit the application of translaminar screw fixation techniques 9 . Conversion to a pedicle screw and revision attempt of the fixation trajectory increased neurovascular injury risk because the small and narrow pedicles are surrounded by vital anatomical structures, such as the central spinal cord, nerve roots, and anterolateral vertebral artery 10 …”
Section: Introductionmentioning
confidence: 99%